Evaluation of a sport-specific field test to determine maximal lactate accumulation rate and sprint performance parameters in running - Quittmann, O. J.; Appelhans, D.; Abel, T.; Strüder, H. (Journal of Science and Medicine in Sport, 2020)
Objectives: The aim of this study was to examine the reliability of maximal lactate accumulation rate (Lamax) and sprint performance parameters in running and assess different approaches to determine alactic time interval (talac). Design: Sixteen competitive runners (female = 5; male = 11) performed three trials (T1, T2 and T3) of an all-out 100-m sprint test separated by 48 h. Methods: Time to cover the 100 m was determined by using a photoelectric light-barrier (t100,LB) and a stop-watch (t100,SW). Throughout the sprints, velocity was measured using a laser velocity guard (LAVEG) to estimate maximal velocity (vmax) and power (Pmax). The talac was calculated as the time when power decreased by 3.5% (tpmax-3.5%) and interpolated based on the sprint time (tinter,LB and tinter,SW). Reliability was assessed using intraclass correlation coefficient (ICC), typical error (TE) and smallest worthwhile change (SWC). Results: After initial familiarisation, t100, tinter, vmax, Pmax and Lamax attained excellent reliability (ICC = 0.90), whereas tpmax-3.5% attained moderate reliability (ICC = 0.518). The reliability of Lamax was higher when tinter,LB or tinter,SW were used (ICC = 0.960) compared to using tpmax-3.5% (ICC = 0.928). At T1, Lamax was significantly higher when stop-watch measurements were used. There was no difference between tpmax-3.5% and the interpolated time intervals and the associated Lamax-estimates. Conclusions: In running, Lamax and sprint performance parameters can easily and high-reliably be measured using this sport-specific field test. Interpolating talac results in similar and more reliable values of Lamax. To improve the reliability and accuracy of the stop-watch estimate, a familiarisation should be performed.